BOShLANGʻICh SINF O‘QUVChILARINI O‘QITIShDA UMUMMILLIY QADIRIYATLAR MOHIYATI - Babasheva, G.B.; Jiyanbayeva, D.Q. (SCIENCE and SOCIETY, 2025)
This article discusses the initiatives being carried out to widely promote national values, the importance of each value in the upbringing of youth, and the development of new methods for teaching these values. It also focuses on explaining the significance of national values to the younger generation and teaching them to cherish and preserve these values.